The Responsibility Of A Shop House Tenant (Ruko) If Demage Happen When The Rental Agreement Ends - Minstyn Tambunan (Journal of Law Science, 2021)
In the era of increasing population growth, the need for housing is also increasing, but the area of ??land needed is decreasing, for that, the way to overcome this is to build houses or shop houses for rent. However, not all people can afford to build these houses or shophouses. Therefore, a house or shophouse rental agreement was made. The problem in this study is how the procedure for a shop house rental agreement occurs between the parties, what are the rights and obligations of the parties in the shophouse rental agreement and what is the responsibility of the shop house tenant if it occurs. damage when the lease agreement expires. This research was conducted in the city of Medan.This research is descriptive. The approach method used is the normative juridical method and the empirical juridical method. The data used are primary data and secondary data. Data collection methods are library data and field studies. Data were collected using a questionnaire. After collecting the data, it was analyzed qualitatively.The shophouse rental agreement entered into by the parties begins with an agreement which is then included in a contract that they have drawn up themselves. The shop owner's obligations are to provide shop-houses that are suitable for use, hand over shop-keys, provide supporting facilities (for example: water, PAM, electricity and telephone), not to lease back to other parties during the current lease period, ask the tenant whether this is done extension of the lease at the shophouse and submit supporting documents in the agreement. Meanwhile, the tenant's obligation is to pay the rent for the shop, to maintain the condition of the shop properly, to pay the budget for the tenant's fees (for example: water, electricity and telephone). If there is damage to the shop at the time the lease agreement ends